Gamification in education—teachers’ perspectives through the lens of the theory of planned behavior - Leiss, Laura; Großschedl, Jörg; Wilde, Matthias; Fränkel, Silvia; Becker-Genschow, Sebastian; Großmann, Nadine (Frontiers in Psychology, 2025)
IntroductionGamification has become an important topic in research, as it is increasingly applied in school lessons. However, gamification is still evolving as a research field, and the investigation of the conditions for and effects of its application on students is just beginning. Previous research on teacher-related conditions for the successful implementation of gamification often lacks a theoretical foundation. The current study aims to close this gap by using the theory of planned behavior to explore teacher variables that impact the use of gamification in class.MethodsFor this purpose, 196 teachers (41.80 ± 10.90 years; 70.9% female) were surveyed regarding the constructs anchored in this theory in an online questionnaire.Results and discussionThe results reveal that teachers’ attitude toward gamification, their perceived subjective norm, and their perceived self-efficacy regarding the implementation of gamification are important predictors of their intention to use gamification in class. However, none of these variables predicted the actual application of gamification in class. Instead, we found mediating effects of teachers’ intention in the relationship between their attitude and behavior. In addition, moderating effects of self-efficacy were observed in the relationship between attitude and intention. Beyond these moderations, intention was found to be a direct predictor of behavior. Our results provide important insights for promoting the application of gamification in schools and for designing teacher training measures.